2015
DOI: 10.1371/journal.pone.0120303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Therapeutic Efficacy of Sequential Therapy Involving Percutaneous Microwave Ablation in Combination with 131I-Hypericin Using the VX2 Rabbit Breast Solid Tumor Model

Abstract: PurposeCombination of percutaneous microwave ablation (PMWA) and intravenous injection of 131I-hypericin(IIIH) may bear potential as a mini-invasive treatment for tumor. The objective of this study was to assess the effect of PMWA and IIIH in breast tumor growth.MethodsTen New Zealand White rabbits bearing VX2 breast carcinomas were randomly divided into two groups (each 5 examples) and processed using PMWA followed by IIIH and IIIH alone. The IIIH activity was evaluated using planar scintigraphy, autoradiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Currently, MWA has been explored in clinical practice, which destroys tumors in situ by means of thermal coagulation or protein denaturation (10). Several studies reported successful experience in the treatment of small breast cancer by using MWA (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MWA has been explored in clinical practice, which destroys tumors in situ by means of thermal coagulation or protein denaturation (10). Several studies reported successful experience in the treatment of small breast cancer by using MWA (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its potential for imaging necrotic myocardium after labeled with iodine-12354., 55., 56., Hyp had also been extensively explored for the treatment of diverse solid tumors or evaluation of therapeutic efficacy after labeled with iodine-131 or copper-64 (Fig. 1)57., 58., 59., 60., 61., 62., 63., 64., 65.. Despite the substantial translational potential related to certain oncological and non-oncological applications 66 , some inherent defects such as extremely poor water solubility, easy to form aggregates and deep colors may haunt its further clinical transformation.…”
Section: Molecular Imaging and Therapeutic Strategies Targeting Necromentioning
confidence: 99%
“…Better than mice model, rabbits are more suitable to establish the orthotopically xenografted tumor and the tumor could also be larger. To sum up, orthotopic tumors on rabbits are more similar to the clinical human tumor [15]. However, the fast development of tumor and high-rate of tumor recurrence on rabbits hinders the phototherapy from big animal modal.…”
Section: Introductionmentioning
confidence: 99%